Socjologiczna analiza partycypacji Państwowej Straży Pożarnej w ochronie ludności w stanach nadzwyczajnych - Maciejewski, Jan; Stochmal, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article has a theoretical character — it is based mainly on the presentation of sociology of dispositional groups. The text represents the complexity of the system of state security and the role of actors involved in providing safety. Academic considerations are placed in a sociological orientation enabling a uniform explanation of phenomena related to the state of emergency. The essence of social dispositional groups is presented on the example of The State Fire Service.
Keywords: Państwowa Straż Pożarna; analiza socjologiczna; ochrona ludności; stany nadzwyczajne